Effect of the addition of nanosilica particles on the properties of two cementitious matrices - Gómez-Zamorano, L. Y.; Castillo-Linton, C. E. (Revista ALCONPAT, 2016)
This research focused on evaluating the effect of adding silica nanoparticles (NS) to two cementitious matrices, as ordinary portland and sulfoaluminate cement, in order to establish their influence on the mechanical and chemical properties. To conduct this evaluation, the NS were added in dosages of 0.30-to-5.0% by mass relative to cement. The results indicated that the compressive strength and resistance to chemical attack by sulfates were improved due to the addition of silica nanoparticles, in both matrices. Finally, the resistance to chemical attack by sulfates showed an improvement with the addition of silica nanoparticles when comparing with pure cement, suggesting an increase in the densification.Keywords: reactivity; supplementary cementitious materials.